Platelet-derived extracellular vesicles promote osteoinduction of mesenchymal stromal cells - Miquel Antich-Rosselló; Maria Antònia Forteza-Genestra; Javier Calvo; Antoni Gayà; Marta Monjo; Joana M. Ramis (Bone & Joint Research, 2020)
Aims: Platelet concentrates, like platelet-rich plasma (PRP) and platelet lysate (PL), are widely used in regenerative medicine, especially in bone regeneration. However, the lack of standard procedures and controls leads to high variability in the obtained results, limiting their regular clinical use. Here, we propose the use of platelet-derived extracellular vesicles (EVs) as an off-the-shelf alternative for PRP and PL for bone regeneration. In this article, we evaluate the effect of PL-derived EVs on the biocompatibility and differentiation of mesenchymal stromal cells (MSCs). Methods: EVs were obtained first by ultracentrifugation (UC) and then by size exclusion chromatography (SEC) from non-activated PL. EVs were characterized by transmission electron microscopy, nanoparticle tracking analysis, and the expression of CD9 and CD63 markers by western blot. The effect of the obtained EVs on osteoinduction was evaluated in vitro on human umbilical cord MSCs by messenger RNA (mRNA) expression analysis of bone markers, alkaline phosphatase activity (ALP), and calcium (Ca2+) content. Results: Osteogenic differentiation of MSCs was confirmed when treated with UC-isolated EVs. In order to disprove that the effect was due to co-isolated proteins, EVs were isolated by SEC. Purer EVs were obtained and proved to maintain the differentiation effect on MSCs and showed a dose-dependent response. Conclusion: PL-derived EVs present an osteogenic capability comparable to PL treatments, emerging as an alternative able to overcome PL and PRP limitations.